2015
DOI: 10.1007/s10967-015-4290-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of a single vial AMBA kit for 68Ga labeling with potential for imaging of GRP receptor-positive cancers

Abstract: This study describes the development of a lyophilized kit formulation of AMBA (DO3A-CH 2 CO-G-[4-aminobenzoyl]-QWAVGHLM-NH 2 ), a bombesin analog, for labeling with 68 Ga from an in-house nanoceriapolyacrylonitrile based 68 Ge/ 68 Ga generator and from a commercial 68 Ge/ 68 Ga generator, for imaging the gastrinreleasing peptide (GRP) receptors over-expressed in a variety of human cancers. 68 Ga-AMBA could be prepared in high radiochemical purity (97 ± 1.1 %) and exhibited high in vitro stability. Biodistribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Besides [ 68 Ga]Ga-RM2, several other cold kit formulations have been reported with GRPR-addressed peptides. Pandey et al described a kit formulation with GRPR agonist [ 68 Ga]Ga-AMBA ([ 68 Ga]Ga-DO3A-CH 2 CO-G-[4-aminobenzoyl]-QWAVGHLM-NH 2 ), while Satpati et al reported the labeling of the antagonist RM26 (D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH 2 ), conjugated either with a NODAGA or an HBED-CC chelator ( 81 , 151 ). Another promising bombesin derivative is the antagonist NeoBomb1.…”
Section: Cold Kitsmentioning
confidence: 99%
“…Besides [ 68 Ga]Ga-RM2, several other cold kit formulations have been reported with GRPR-addressed peptides. Pandey et al described a kit formulation with GRPR agonist [ 68 Ga]Ga-AMBA ([ 68 Ga]Ga-DO3A-CH 2 CO-G-[4-aminobenzoyl]-QWAVGHLM-NH 2 ), while Satpati et al reported the labeling of the antagonist RM26 (D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH 2 ), conjugated either with a NODAGA or an HBED-CC chelator ( 81 , 151 ). Another promising bombesin derivative is the antagonist NeoBomb1.…”
Section: Cold Kitsmentioning
confidence: 99%
“…A lyophilized kit of bombesin agonist, AMBA (DO 3 A-CH 2 CO-G-[4-aminobenzoyl]-QWAVGHLM-NH 2 ), for 68 Ga-labeling has been reported by Pandey et al Kits were validated with an in-house-developed nanoceria–polyacrylonitrile (ceria–PAN) based 68 Ge/ 68 Ga generator. Prior to kit formulation, manual (wet labeling) experiments were performed to optimize the kit components and the radiolabeling conditions.…”
Section: Ga-kits: Nuclear Medicine Applicationsmentioning
confidence: 99%